UHPLC/PDA–ESI/MS Analysis of the Main Berry and Leaf Flavonol Glycosides from Different Carpathian Hippophaë rhamnoides L. Varieties. Issue 5 (27th August 2013) - Pop, Raluca Maria; Socaciu, Carmen; Pintea, Adela; Buzoianu, Anca Dana; Sanders, Mark Gerardus; Gruppen, Harry; Vincken, Jean‐Paul; de, Victor; Comte, Gilles; Santos‐Buelga, Celestino
ABSTRACT Introduction Sea buckthorn (Hippophaë rhamnoides L.) is known to be rich in many bioactive compounds (such as vitamins, phenolics, carotenoids) important for human health and nutrition. Among the phenolics, berries and leaves contain a wide range of flavonols that are good quality and authenticity biomarkers. Objective To compare the composition of the main flavonols of Romanian sea buckthorn berry and leaf varieties and to identify the specific biomarkers that contribute to sample differentiation among varieties. Material and methods Six varieties of cultivated sea buckthorn (ssp. Carpatica) berries and leaves were analysed by UHPLC/PDA–ESI/MS. Results Berries and leaves contained mainly isorhamnetin (I) glycosides in different ratios. Whereas I‐3‐neohesperidoside, I‐3‐glucoside, I‐3‐rhamnosylglucoside, I‐3‐sophoroside‐7‐rhamnoside and free isorhamnetin were predominant for berries (out of 17 compounds identified), I‐3‐rhamnosylglucoside, I‐3‐neohesperidoside, I‐3‐glucoside, quercetin‐3‐pentoside, kaempferol‐3‐rutinoside, and quercetin‐3‐glucoside were predominant in leaves (out of 19 compounds identified). Berries contained, on average, 917 mg/100 g DW flavonol glycosides. Leaves had higher content of flavonol glycosides than berries, on average 1118 mg/100 g DW. The variation of the quantitative dataset analysed using principal component analysis accounted for 91% of the total variance in the case of berries and 73% in case of leaves, demonstrating a good discrimination among samples. Conclusion Based on quantitative analysis, by principal component analysis, the flavonol derivatives can be considered as biomarkers to discriminate among varieties and to recognise specifically the berry versus leaf composition. Copyright © 2013 John Wiley & Sons, Ltd.